2016
DOI: 10.3847/0004-637x/823/1/33
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Mixing by Double-Diffusive Convection (Semi-Convection). Iii. Thermal and Compositional Transport Through Non-Layered Oddc

Abstract: Oscillatory double-diffusive convection (ODDC; also known as semi-convection) refers to a type of doublediffusive instability that occurs in regions of planetary and stellar interiors that have a destabilizing thermal stratification and a stabilizing mean molecular weight stratification. In this series of papers, we use an extensive suite of three-dimensional (3D) numerical simulations to quantify the transport of heat and chemical species by ODDC. Rosenblum et al. first showed that ODDC can either spontaneous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
2
41
0
1
Order By: Relevance
“…Importantly, as with the non-rotating simulation, layers never form at any point (when R −1 0 = 4.25). Consequently, fluxes through non-layered (high R −1 0 ) systems are effectively diffusive, and the conclusion from Moll et al (2016), namely that turbulent fluxes are negligible for non-layered systems, remains valid for all the simulations presented here.…”
Section: Simulations At Largesupporting
confidence: 58%
“…Importantly, as with the non-rotating simulation, layers never form at any point (when R −1 0 = 4.25). Consequently, fluxes through non-layered (high R −1 0 ) systems are effectively diffusive, and the conclusion from Moll et al (2016), namely that turbulent fluxes are negligible for non-layered systems, remains valid for all the simulations presented here.…”
Section: Simulations At Largesupporting
confidence: 58%
“…For instance, following comparisons between 2D and 3D direct numerical simulations of convection with a composition gradient of an active scalar (i.e., a gradient of helium in a mixture of hydrogen and helium in the case of a star), it was found that while layered semi-convection may well be investigated and quantitatively be described by 2D simulations (Moll et al. 2016 ), this is not the case in the fingering regime (Garaud and Brummell 2015 ). The latter can appear when the composition gradient drives the convective instability and is counteracted by the temperature gradient, which is just the other way round for layered semi-convection.…”
Section: What Is the Difficulty With Convection?mentioning
confidence: 99%
“…That is, in this region, helium becomes insoluble in hydrogen and gravitationally falls through the fluid, which produces a stable layer with heavy fluid below light fluid. There may also be double-diffusive instabilities occurring below this layer due to very different molecular diffusion rates of temperature and heavy element composition in a region with a destabilizing (superadiabatic) thermal stratification and a stabilizing mean molecular weight stratification ( 31 ).…”
Section: Discussionmentioning
confidence: 99%